THE PRINCIPLES OF LAW. PHILOSOPHICAL APPROACH - MARIUS ANDREESCU (Challenges of the Knowledge Society, 2013)
Any scientific intercession that has as objective, the understanding of the significances of the “principle of law” needs to have an interdisciplinary character, the basis for the approach being the philosophy of the law. In this study we fulfill such an analysis with the purpose to underline the multiple theoretical significances due to this concept, but also the relationship between the juridical principles and norms, respectively the normative value of the principle of the law. Thus are being materialized extensive references to the philosophical and juridical doctrine in the matter. This study is a pleading to refer to the principles, in the work for the law’s creation and applying. Starting with the difference between “given” and ‘constructed” we propose the distinction between the “metaphysical principles” outside the law, which by their contents have philosophical significances, and the “constructed principles” elaborated inside the law. We emphasize the obligation of the law maker, but also of the expert to refer to the principles in the work of legislation, interpretation and applying of the law. Arguments are brought for the updating, in certain limits, the justice – naturalistic concepts in the law.